Mineral elements in follicular fluid of buffalo ovary - KAUR, JAGJIT; TAKKAR, O P; KHERA, K S; CHAUDHARY, K C; SINGH, RAJVIR (The Indian Journal of Animal Reproduction, 2023)
• lnvestigatipns were conducted on 250 buffalo ovaries bearing vesicular follicles procured from slaughter house to study mineral elements in the follicular fluid. The concentration of sodium (Na•) increased in large follicles (75±4.2 ug ml). In small and medium follicles it was significantly less (25±2.4 .. 25±2.9 ug ml) whereas the concentration of Mg++ and Zn++ decreased in large follicles as compared to small and medium follicles. A corresponding increase in cacium (Ca++) was observed in large follicles than small and medium sized follicles. No significant change has been found in value of · Cu++ all the three categories.